1986
DOI: 10.1111/j.1600-079x.1986.tb00748.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Melatonin, Serotonin, and Naloxone on Aggression in Isolated Cichlid Fish (Aequidens pulcher)

Abstract: Intracranial injections of 10 micrograms melatonin, with or without 4 micrograms naloxone, result in reduced aggressive responsiveness by the cichlid fish Aequidens pulcher to a mirror presented 20 min later. Naloxone, when administered on its own, had no behavioral effect. Intracranial injections of 25 micrograms serotonin-creatinine sulphate complex (5HT-CS) also reduced aggression. 5HT-CS's action was abolished if the injection included 10 micrograms S-adenosyl homocysteine (SAH), which inhibits the convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
5

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 9 publications
2
42
0
5
Order By: Relevance
“…ICER plays a key role in circadian melatonin synthesis by repressing the key enzyme that converts serotonin to melatonin [81]. High levels of these neurotransmitters have been associated with increased mating and cooperative behavior and decreased aggressive behavior [82][83][84]. ICER has not yet been well characterized in teleosts but one of our differentially expressed crem transcripts had a significant blast hit to an ICER variant from Epinephelus brunes (longtooth grouper).…”
Section: Candidate Genes Associated With Artsmentioning
confidence: 99%
“…ICER plays a key role in circadian melatonin synthesis by repressing the key enzyme that converts serotonin to melatonin [81]. High levels of these neurotransmitters have been associated with increased mating and cooperative behavior and decreased aggressive behavior [82][83][84]. ICER has not yet been well characterized in teleosts but one of our differentially expressed crem transcripts had a significant blast hit to an ICER variant from Epinephelus brunes (longtooth grouper).…”
Section: Candidate Genes Associated With Artsmentioning
confidence: 99%
“…MUNRO (1986) observou no ciclídeo Aequidens pulcher, o papel deste hormônio na redução de respostas agressivas. Alguns estudos com trutas e salmãos do Atlântico expostos ao período noturno, verificaram que o aumento da intensidade de luz gera uma diminuição dos níveis de melatonina (ZACHMANN et al, 1992;PORTER et al, 2001).…”
Section: Resultsunclassified
“…The higher consumption and glycine tryptophan by fish, it tends to the production of serotonin in the brain also increases [16]. Munro [20] and Maler & Ellis [21] reported that the higher the levels of serotonin in the brain, then the level of aggressive fish tends to decrease. In this study, it can be estimated that the aggressiveness of giant prawn seed tends to decrease with the addition of tryptophan and glycine as much as 1.0% in the feed.…”
Section: Resultsmentioning
confidence: 99%